A corrole-based fluorescent probe for detection of sulfur ion and its application in living cells. (January 2022) - Lu, Guifen; Gao, Yongjie; Wang, Xiaochun; Zhang, Dianqi; Meng, Suci; Yu, Siyuan; Zhuang, Yanfang
Abstract: A dual signaling probe DPC-O-NBD formed through the conjugation of 5, 15-bis(phenyl)-10-(4-hydroxylphenyl)-corrole (DPC-OH) with 4-chloro-7-nitrobe-nzo-2-oxa-1, 3-diazole (NBD-Cl) is explored to detect sulfur ion (S 2− ). The key design principle is based on the nucleophilicity of S 2−, which can be used to cleave the bridging ether bond in the probe to obtain both fluorogenic and chromogenic signaling behaviors. Importantly, the probe DPC-O-NBD not only showed a high sensitivity (LOD: 48 nM) and selectivity over other interfering species, but also exhibited a rapid response (∼18 s) towards S 2− . Furthermore, DPC-O-NBD can also be used to detect S 2− in both water and live cells, providing a potentially powerful approach for probing S 2− chemistry in biological systems. Graphical abstract: A sensitive and selective dual signaling probe, DPC-O-NBD, was designed and prepared for the detection of sulfur ion with a fast response (∼18 s) and a low detection limit (48 nM). This probe was successfully applied for imaging of S 2− in both water and Hela cells. Image 1 Highlights: A dual signaling probe for detection of sulfur ion based on corrole was reported. The probe towards S 2− showed both fluorogenic and chromogenic signaling behaviors. The probe exhibited remarkable properties including fast response, high selectivity and good biocompatibility. The probe was successfully used for imaging S 2− in both water and HeLa cells.